On the Stability of Trigonometric Functional Equations in Distributions and Hyperfunctions - Jaeyoung Chung; Jeongwook Chang (Abstract and Applied Analysis)
We consider the Hyers-Ulam stability for a class of trigonometric functional equations in the spaces of generalized functions such as Schwartz distributions and Gelfand hyperfunctions.